Adult lifetime body mass index trajectories and endometrial cancer risk. (18th January 2022) - Dalmartello, Michela; Vermunt, Jeroen; Negri, Eva; Levi, Fabio; La Vecchia, Carlo
Abstract: Objective: To identify body mass index (BMI) trajectories in adult life and to examine their association with endometrial cancer (EC) risk, also exploring whether relations differ by hormonal replacement therapy use. Design: Pooled analysis of two case–control studies. Setting: Italy and Switzerland. Population: A total of 458 EC cases and 782 controls. Methods: We performed a latent class growth model to identify homogeneous BMI trajectories over six decades of age, with a polynomial function of age. Odds ratios (ORs) and the corresponding 95% CI for EC risk were derived through a multiple logistic regression model, correcting for classification error. Main outcome measures: The relation of BMI trajectories with endometrial cancer. Results: We identified five BMI trajectories. Compared with women in the 'Normal weight‐stable' trajectory, a reduction by about 50% in the risk of EC emerged for those in the 'Underweight increasing to normal weight' (95% CI 0.28–0.99). The 'Normal weight increasing to overweight' and the 'Overweight‐stable' trajectories were associated with, respectively, an excess of 3% (95% CI 0.66–1.60) and of 71% (95% CI 1.12–2.59) in cancer risk. The OR associated to the trajectory 'Overweight increasing to obese' was 2.03 (95% CI 1.31–3.13). Stronger effects emerged among hormonal replacement therapy never users (OR 2.19 for the 'Overweight‐stable' trajectory and OR 2.49 for the 'Overweight increasing to obese' trajectory). Conclusions: Our study suggests that longer exposure to overweight and obesity across a lifetime is associated with an increased risk of endometrial cancer. Weight during adulthood also appears to play an important role. Tweetable abstract: Longer exposure to overweight and obesity across a lifetime is associated with an increased risk of endometrial cancer. Tweetable abstract: Longer exposure to overweight and obesity across a lifetime is associated with an increased risk of endometrial cancer.